PERLINDUNGAN HUKUM BAGI KONSUMEN DARI PEREDARANOBAT ILEGAL PADA E-COMMERCE : Studi Kebijakan PPKMPada Masa Pandemi COVID-19 - Muhammad Fadillah Ulhad (2023)
PPKM has increased drug purchases through e-commerce as an alternative to shopping, and unscrupulous persons can exploit this phenomenon by selling illegal drugs. This study aims to find out why there is still circulation of illegal drugs through e-commerce which can be detrimental to consumers. This study uses a normative juridical method by conducting research based on literature studies in the form of laws and official press releases from BPOM. The approach used is a statutory and case approach with legal materials from BPOM press releases. The type of data used is secondary data consisting of primary and secondary legal materials. The conclusion drawn from this research is that PPKM factors and supervision factors from BPOM influence illegal drug distribution. Besides that, there are regulations from BPOM regarding online drug distribution, which can protect consumers. Based on this, consumers are expected to be smart consumers. Consumers must understand the principle of caution when shopping for drugs online. BPOM RI is expected to be able to provide solutions to eradicate the circulation of illegal drugs so that consumers do not have to suffer losses first. There is a need to increase cooperation with e-commerce parties in prevention, supervision and prosecution so that no businessman dares to sell illegal drugs. Keywords : Consumer, Illegal Drugs, E-commerce, PPKM